Young people's understandings of men's violence against women - Lombard, Nancy (Ashgate, 2015)
Violence -- Childhood -- Research methodology -- Gender constructions -- "Real" violence by "real" men : naturalising masculinity -- Processes of normalisation : distancing "unreal" and "proximate" violence -- Heterosexuality, gender and adulthood : justifications of violence -- Some conclusions and recommendations